Strategi Peningkatan Akreditasi Pada Lembaga Pendidikan Di MTs Negeri 2 Bandar Lampung - Adam Rival Rizkyan; Ilhami (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
This study aims to analyze strategies for improving accreditation in educational institutions at MTs Negeri 2 Bandar Lampung. The research focuses on institutional efforts to maintain and enhance educational quality to achieve excellent accreditation standards set by the National Accreditation Board for Schools/Madrasahs (BAN-S/M). This qualitative descriptive study employed a case study approach. Data were collected through interviews, observations, and documentation involving the principal, vice principal for curriculum, and administrative staff. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that accreditation improvement strategies were implemented through three main approaches: consistency in quality-oriented programs, realistic planning aligned with institutional resources, and careful management of teachers and educational staff. These strategies contributed significantly to sustaining excellent accreditation and strengthening institutional quality